Transbronchial lung cryobiopsy in idiopathic acute fibrinous and organizing pneumonia. (2019) - Shintani, Ryota; Oda, Tsuneyuki; Niwa, Takashi; Sekine, Akimasa; Hagiwara, Eri; Okudela, Koji; Takemura, Tamiko; Ogura, Takashi
Abstract: A 53-year-old Japanese female was admitted to our hospital with 3-week history of cough and worsening dyspnea. Chest computed tomography revealed unilateral focal consolidation in the right lower lobe. She underwent transbronchial lung cryobiopsy (TBLC) and histology showed acute fibrinous and organizing pneumonia (AFOP). High-dose methylprednisolone treatment improved her respiratory condition and radiological findings. AFOP is a rare histologic interstitial pneumonia pattern and has been diagnosed by surgical lung biopsy or autopsy in most cases. To our knowledge, this is the first detailed report of AFOP diagnosed by TBLC. TBLC can be performed safely with less invasion and be a useful diagnostic technique for rapidly progressive diffuse lung disease such as AFOP.